2018
DOI: 10.1016/j.future.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Keeping up with storage: Decentralized, write-enabled dynamic geo-replication

Abstract: Large-scale applications are ever-increasingly geo-distributed. Maintaining the highest possible data locality is crucial to ensure high performance of such applications. Dynamic replication addresses this problem by dynamically creating replicas of frequently accessed data close to the clients. This data is often stored in decentralized storage systems such as Dynamo or Voldemort, which offer support for mutable data. However, existing approaches to dynamic replication for such mutable data remain centralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Many efforts have been made to propose and develop different dynamic data replication algorithms, such as 17 , 44 46 . A prefetching-aware data replication (PDR) strategy was proposed in Ref.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts have been made to propose and develop different dynamic data replication algorithms, such as 17 , 44 46 . A prefetching-aware data replication (PDR) strategy was proposed in Ref.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, it replaces the unnecessary replicas with the more popular replicas to save the storage space of each node. To leverage the decentralized architecture of decentralized storage systems such as Dynamo 47 or Voldemort 48 , Matri et al 44 proposed a write-enabled dynamic replication scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Matri et al suggested a decentralized, write-enabled dynamic geo-replication (DWEDGR) approach. DWEDGR lets users to connect to the closest replication between nodes without having to make a prior request for data that can be changed [45].…”
Section: Related Workmentioning
confidence: 99%
“…Matri et al [38] proposed a model for data de-duplication with a classified client-server. This model aims to reduce the delay in data access.…”
Section: Classified Client-server Architecturementioning
confidence: 99%